Training, education, and outreach—raising the bar. (6th March 2014) - Akli, Linda; Moore, Samuel L.; Rivera, Lorna I.; Teller, Patricia J.; Wilkins‐Diehr, Nancy; Majumdar, Amit
SUMMARY To accelerate scientific discovery, the Extreme Science and Engineering Discovery Environment (XSEDE) aims to enhance researcher productivity, increase its user base, and prepare new generations of researchers to use advanced digital technologies. Accordingly, XSEDE is educating diverse populations of new users through regional workshops targeted at large populations of those traditionally underrepresented in the use of XSEDE resources. The expanded scale and scope of recent workshops provide evidence that (1) there is strong interest in leveraging advanced digital services in research and teaching at minority‐serving institutions; (2) these local events are needed to reach these communities; and (3) increased collaboration is required to inculcate the use of computational methods into research and teaching at these institutions. This makes it clear that XSEDE's efforts are meaningful beyond just providing training in advanced digital services; they contribute to national goals for developing and sustaining a large and diverse STEM workforce. This paper focuses on the first of the larger workshops (held at The University of Texas at El Paso) and its impact on subsequent events. Best practices used to plan, execute, and evaluate this workshop are discussed, and the results of a professional assessment of the three workshops are presented. Copyright © 2014 John Wiley & Sons, Ltd.